(untitled) (Research, Society and Development, 2020)
Abortion is defined as an interruption of pregnancy with expulsion of the concept, which according to the World Health Organization must be until the 22nd week of gestation or with the expelled product weighing less than 500 grams. Despite underreporting, abortion remains an important obstetric complication, responsible for the large number of hospitalizations and maternal death. The objective was to analyze nursing assistance on the care provided as women undergoing an abortion process, according to scientific research. An Integrative Literature Review was carried out, using a search protocol adapted for collecting secondary data and categorical thematic analysis of the content. A sample consisted of 30 articles, as the approaches were categorized for the following titles: “Abortion and social stigma”; “Abortion from the perspective of nursing: expectation and reality”; “Care management: health care in the abortion process”; “Ideal assistance: what needs to be improved?”. Assistance to women in abortion was identified as still very fragmented.